ANALISIS KINERJA PENEGAKAN HUKUM DALAM MENURUNKAN KASUS PERDAGANGAN ILLEGAL SATWA YANG DILINDUNGI DI PROVINSI KALIMANTAN BARAT - Rachmad, Rachmad; Prayogo, Hari; Anwari, M Sofwan (Universitas Tanjungpura, 2021)
This research is motivated by the high cases of illegal trade of protected wildlife in West Kalimantan Province. Animal trade tends to be endangered and included in the endangered list. Actions of animal trade that still occur in West Kalimantan Province indicate the low level of law enforcement and weak supervision by related parties in combating cases of protected animal trade. The purpose of this study is to examine the factors causing the occurrence of illegal trade crimes against protected animals in the West Kalimantan region, and analyze the performance of stakeholders in law enforcement against the illegal trade of protected animals in the West Kalimantan region based on their role and authority. This study uses a survey method that is guided by a questionnaire. The selection of respondents by purposive sampling, data analysis using policy analysis then the data is descriptive with tabulation. The results of the study show that in the period of 2016-2019 there were 49 cases of illegal wildlife trade in West Kalimantan Province, the traded animals are species belonging to protected animals and classified in the Appendix I. category. The dominant protected species traded in the 2016-2019 period originated from anteater species (Manis javanica), Orang-utan (Pongo pygmaeus), and Turtle (Chelonia sp.). The dominant factor in the illegal trade of protected animals in the province of West Kalimantan in the 2016-2019 period was economic factors, followed by motives for the collection of rare goods and consumption. The performance of stakeholders in law enforcement against protected animals in the West Kalimantan region has succeeded in handling criminal cases against protected animals, all of which ended with the execution of the defendant.Keywords: law enforcement performance, protected animals, illegal trading, stakeholders.AbstrakPenelitian ini dilatarbelakangi tingginya kasus perdagangan illegal satwa dilindungi di Provinsi Kalimantan Barat. Perdagangan satwa yang dilakukan cenderung pada spesies-spesies langka dan termasuk dalam daftar terancam punah. Aksi perdagangan satwa yang masih terjadi di Provinsi Kalimantan Barat mengindikasikan masih rendahnya penegakan hukum dan lemahnya pengawasan oleh pihak terkait dalam memberantas kasus perdagangan satwa yang dilindungi. Tujuan penelitian ini untuk mengkaji faktor penyebab terjadinya kejahatan perdagangan illegal terhadap satwa yang dilindungi, serta menganalisis kinerja pemangku kepentingan dalam penegakan hukum terhadap perdagangan illegal satwa yang dilindungi di wilayah Kalimantan Barat berdasarkan peran dan kewenangan. Penelitian ini menggunakan metode survey yang dipandu dengan kuesioner. Pemilihan responden dengan purposive sampling, analisis data menggunakan analisis kebijakan kemudian data dideskriptif dengan tabulasi. Hasil penelitian menunjukan kurun waktu 2016-2019 terdapat 49 kasus perdagangan satwa illegal di Provinsi Kalimantan Barat, satwa yang diperdagangkan merupakan jenis satwa yang termasuk ke dalam satwa dilindungi dan tergolong dalam kateogri Appindiks I. Satwa dilindungi dominan yang diperdagangkan pada periode 2016-2019 berasal dari spesies trenggiling (Manis javanica), Orang utan (Pongo pygmeus), dan Penyu (Chelonia sp.). Faktor dominan perdagangan illegal satwa dilindungi di Provinsi Kalimantan Barat dalam periode 2016-2019 adalah faktor ekonomi kemudian diikuti motif koleksi barang langka dan konsumsi. Kinerja pemangku kepentingan dalam penegakan hukum terhadap satwa yang dilindungi di wilayah Kalimantan Barat, telah berhasil menangani kasus pidana terhadap satwa dilindungi yang kesemuanya berahir dengan eksekusi kepada terdakwa.Kata kunci: kinerja penegakan hukum, perdagangan illegal, satwa dilindungi, pemangku kepentingan.